The persecution of the Knights Templar scandal, torture, trial - Demurger, Alain 1939- (Pegasus Books, 2019)
A history of the infamous trial of the Order of the Knights Templar draws on firsthand testimonies and written records to chronicle the early plots of 1305, the tortured confessions of arrested Templars, and the executions of order leaders
Keywords: Templerorden; Geschichte 1307-1314; Prozess; Verfolgung; Templars / History; Templars / Trials, litigation, etc; Templars; History; Trials, litigation, etc